Heavy metal concentration in the surface sediment of Tanjung Lumpur Mangrove Forest, Kuantan, Malaysia - Kamaruzzaman Yunus,; Nurulnadia Mohd Yusuf,; Noor Azhar Mohd Shazili,; Ong, Meng Chuan; Shahbudin Saad,; Ahmed Jalal Khan Chowdhury,; Joseph Bidai, (Universiti Kebangsaan Malaysia, 2011)
Surface sediment samples from 2 transects (20 sampling points) of Tanjung Lumpur mangrove forest were analyzed for the concentrations of Pb, Cu, Co and Mn. In this study, the average concentrations of Pb, Cu, Co and Mn were 44.41 μg/g dry weight, 32.79 μg/g dry weight, 5.79 μg/g dry weight and 117.73 μg/g dry weight, respectively. The calculated enrichment factors (EF) obtained for Co and Mn can be considered to have the terigeneous in sources while Pb and Cu are considered to have anthropogenic input.